A study of the ignition delay characteristics of combustion in a compression ignition engine operating on blended mixtures of diesel and gasoline - Thoo, Wei Jet (2016)
The interest to study diesel-gasoline fuel mix for CI engine combustion had been motivated by the higher thermal efficiency of CI engine compared to SI engine which gasoline normally runs in and the report of having lower NOx and PM emissions for gasoline combustion in CI engine. The experimental CI engine was unable to run on 100% gasoline but able to run on gasoline blend as high as G80 with default SOI timing setting. 100% gasoline would not run despite it contains only 20% more gasoline than G80 due to its extremely longer ignition delay caused by the exponential increase of gasoline blend’s ID. Engine brake thermal efficiencies of all gasoline blends tested up to G80 were comparable and averaged at 24.2%, 33.8% and 39.8% for engine speed-load conditions of 2000rev/min 2.5bar BMEP, 2000rev/min 5bar BMEP and 2000rev/min 8.5bar BMEP, accordingly. This finding confirmed that gasoline blend could be a new alternative fuel that offers comparable performance to the liquid fuel market for CI engine. In Europe, diesel blended with a small percentage of biodiesel or ethanol has been common to liquid fuel market.